Geophysical 2d Self-Potentials And Earth Resistivity Survey Over Slope Stability Study - Bakari, Maisarah Ahmad (Universiti Sains Malaysia, 2017)
In this project, geophysical methods of self-potential and electrical resistivity survey are joined to study slope stability at Kampung Sungai Buaya, Nibong Tebal, Penang. Generally, the geological structure of this town consists of quaternary unconsolidated deposit which refers to loose materials, ranging from clay, sand to gravel underlain by granitic bedrock. The study site is a natural ground slope and the soil type within the slope is brownish sandy to sandy clay. The slope angle was 300 in the direction towards west and located in a vegetated area. Slope stability is affected by many factors namely the slope angle, rainfall distribution and groundwater, type of material within slope and vegetation. SP and resistivity surveys are applied to investigate the influence of soil properties on slope stability. The surveys are conducted on hot weather and rainy season to observe the water saturation in soil slope. SP results show that water movement down the slope. After rainfall, water saturation increases which leads to weakening of the slope. Near surface materials which are sandy clay soils have low resistivity values indicating the high moisture content. Moderately high resistivity values obtained refer to sandy type of soils. Mixture of sand and clay increases the strength of soil slope materials especially in moist condition due to water surface tension and frictional contact to each other. Vegetation around the study area helps to keep slope in place by roots reinforcement and absorption of excessive water. Thus, it is concluded that the studied soil slope has high stability.